Distribution and abundance of the Neotropical otter (Lontra longicaudis annectens) in Tlacotalpan, Veracruz, Mexico - Arellano Nicolas, Edith; Sánchez-Nuñez, Edmundo; Mosqueda Cabrera, Miguel Ángel (Instituto de Ecología, A.C., 2012)
Presence and abundance of the neotropical otter (Lontra longicaudis annectens) were established in the locality of Tlacotalpan, Veracruz, during north and hurricane seasons in 2007 and dry season in 2008, where it was carried out a monitoring process in two zones (i) the Papaloapan River margins, and (ii) streams and lagoons near to the locality. Furtheremore, interviews to local inhabitants were carried out in order to obtain information about biological aspects of the species based on the local knowledge shown by the inhabitants. On the other hand, 61 feces, 13 latrines, and two borrows were located. Moreover, two individuals were observed and recorded. During November 2007 the abundance recorded in two zones within the study area was 1.22 and 0.61 otters/km. In April 2008 the same two zones showed 0.43 and 0.21 otters/km. Finally, 100% of the interviewees know the river otter, and 99% of them consider that the species is relevant to the aquatic ecosystems and it must be protected.